Transnational Archipelago Perspectives on Cape Verdean Migration and Diaspora - Batalha, Luís; Carling, Jørgen (Amsterdam University Press, 2008)
The island nation of Cape Verde has given rise to a diaspora that spans the four continents of the Atlantic Ocean. Migration has been essential to the island since the birth of its nation. This volume makes a significant contribution to the study of international migration and transnationalism by exploring the Cape Verdean diaspora through its geographic diversity and with a broad thematic range.